The Acceleration Wave in a Thin Two-Material and Three-Segmental Rod with Slowly Changing Cross-Section Made of Murnaghan Material - Izabela Major (Communications - Scientific letters of the University of Zilina, 2014)
The paper presents propagation of acceleration waves in a thin rod with slowly changing cross-section made of hyperelastic Murnaghan material. Analytical calculations were made based on the models obtained for the intensity of the transmitted and reflected wave. Numerical analysis of the velocity of wave propagation in the three-segmental rod made of two compressible elastic materials (steel and aluminum) has been made.